The New TNM Staging System for Thyroid Cancer and the Risk of Disease Downstaging - Casella, Claudio; Ministrini, Silvia; Galani, Alessandro; Mastriale, Francesco; Cappelli, Carlo; Portolani, Nazario (Frontiers in Endocrinology, 2018)
In October 2016 the American Joint Committee on Cancer (AJCC) published the 8th edition of the AJCC/TNM cancer staging system and it has been introduced in clinical practice since 1st January 2018. The effect of most of the changes in the new edition was the downstaging of a significant number of patients into lower stages, reflecting their low risk of thyroid cancer-related death. One of the most relevant modification refers to the role of the microscopic extra-thyroidal tumor invasion, which is no longer considered as criterion for the classification of T3 tumors. With the present study we want to assess the impact of the changes of the new staging system and therefore we analyzed or casistic of 84 T1-T3 thyroid-cancer patients. The results of our analysis show that he downstaging of patients according to the 8th TNM edition does not necessarily reflect less aggressive disease: we actually reported 2 lymph-nodal recurrences (40%) in the 5 patients that were downstaged from pT3 to pT2 and the lypmh-nodal recurrence rate for stage I rises from 0% with the 7th TNM edition to 5,3% with the 8th edition.